Peningkatan Hasil Belajar IPS Perubahan Wilayah Provinsi di Indonesia melalui Media Pembelajaran Interaktif di Kelas VI SDN Jarin 4 Kecamatan Pademawu Kabupaten Pamekasan Tahun Pelajaran 2020/2021 - Mohammad Jahuri (Departement of Mathematics Education, 2023)
As one of the conditions for achieving educational and teaching goals in general is the teacher's ability to select, develop and produce media, elements of methods and media are elements that cannot be separated from elements or techniques to deliver learning material to arrive at the goal. This study aims to: describe the use of interactive learning media to improve social studies learning outcomes in changes in provincial areas in Indonesia, describe the level of mastery of student learning about changes in provincial areas in Indonesia by using interactive learning media in social studies class VI at SDN Jarin 4 Pademawu District. The use of the use of interactive learning media can improve social studies learning outcomes for changes in provincial areas in Indonesia for class VI, the highest score achieved by students reaches 100 (1 person). VI at SDN Jarin 4, Pademawu District. Of the 10 students, there are 90% or 9 students who have completed their studies and only 1 student (10%) has not completed their studies.